THE CHARACTER OF BU PRANI IN THE FILM “BUDI PEKERTI”: A SEMIOTIC ANALYSIS STUDY BY CHARLES SANDERS PEIRCE - Rizki Wahyu Arif Hidayatulloh; Rustim; Choiru Pradhono (EZRA SCIENCE BULLETIN, 2024)
This study aims to reveal the signs of Mrs. Prani's character in the film 'Budi Pekerti' using Charles Sanders Peirce's semiotic analysis. The research method used is descriptive qualitative with an in-depth case study. Data collection techniques include observation, interviews, and documentation. The results of the study show that there are 27 signs that depict the four main characteristics of Mrs. Prani: honest, patient, intelligent, and responsible. These signs were identified through visual and audio analysis of scenes in the film. Peirce's semiotic approach is effective in understanding how visual and audio signs are used to build character and convey moral messages in the film. This research contributes to a deeper understanding of the use of semiotics in film analysis, particularly in analyzing characters and conveying moral messages through visual and audio signs.